2016
DOI: 10.1530/rep-16-0091
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of follicle development in a mouse model of premature ovarian insufficiency

Abstract: Premature ovarian insufficiency (POI) occurs in 1% of reproductive-age women. The ovarian manifestation ranges from the presence of a variable population of follicles (follicular) to the absence of follicles (afollicular), and in the majority of cases the cause is unknown. A transgenic mouse model of follicular POI, the Double Mutant (DM), arises from oocyte-specific deletion of Mgat1 and C1galt1 required for the generation of O- and N-glycans. DM females are subfertile at 6 weeks, infertile by 9 weeks and exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Despite changes in mental and active status, vaginal epithelial cytology smears showing a normal estrous cycle (4–5 days and the estrus period, pre‐estrus, estrus and late‐estrus emerged alternately) were used as exclusion criteria for POI. Previous studies have shown that disordered estrous cycles indicate successful establishment of a POI model . The optimum concentration of tripterygium wilfordii polyglycoside tablets used in this study was based on the rat model of induced POI by Hao Juan…”
Section: Methodsmentioning
confidence: 99%
“…Despite changes in mental and active status, vaginal epithelial cytology smears showing a normal estrous cycle (4–5 days and the estrus period, pre‐estrus, estrus and late‐estrus emerged alternately) were used as exclusion criteria for POI. Previous studies have shown that disordered estrous cycles indicate successful establishment of a POI model . The optimum concentration of tripterygium wilfordii polyglycoside tablets used in this study was based on the rat model of induced POI by Hao Juan…”
Section: Methodsmentioning
confidence: 99%
“…The first of these phenotypes was oocytes trapped within CLs, or luteinized but unruptured follicles. The presence of an oocyte in a CL indicates that the follicle luteinized before rupture and the oocyte was not ovulated [28] ( Figure 5AI). This could be due to follicles that luteinized prior to rupture or luteinization that occurred because follicles failed to rupture.…”
Section: Reproductively Old Mice Exhibit a Greater Percentage Of Failmentioning
confidence: 99%
“…This excess expression of LHR suggested premature luteinization in TGF follicles, which was also demonstrated by the dramatically raised expression of 3βHSD (3β-hydroxysteroid dehydrogenase) in TGF SFs (Fig. 5B)(Grasa et al, 2016). In consideration of the striking features of reduced follicle number and degraded GCs in the TGF follicles, we then detected the expression levels of caspase 3 and Ki67 to assess the cell apoptosis and proliferation activity.…”
Section: Resultsmentioning
confidence: 85%